2015
DOI: 10.1117/1.oe.54.2.026102
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot semiconductor optical amplifier/silicon external cavity laser for O-band high-speed optical communications

Abstract: Abstract. We report a hybrid integrated external cavity laser by butt coupling a quantum dot reflective semiconductor optical amplifier and a silicon-on-insulator chip. The device lasers at 1302 nm in the O-band, a wavelength regime critical to data communication systems. We measured 18 mW on-chip output power and over 50-dB side-mode suppression ratio. We also demonstrated open eye diagrams at 10 and 40 Gb∕s. © The Authors.Published by SPIE under a Creative Commons Attribution 3.0 Unported License. Distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Thus, optical amplifiers are indispensable components in long-range transmission systems. The technologies related to SOAs include optics [2,3], semiconductor [1], material [19], communication [20], and surface treatment [21] technologies. Thus, SOAs constitute an interdisciplinary research topic.…”
Section: Development Status Of Soasmentioning
confidence: 99%
“…Thus, optical amplifiers are indispensable components in long-range transmission systems. The technologies related to SOAs include optics [2,3], semiconductor [1], material [19], communication [20], and surface treatment [21] technologies. Thus, SOAs constitute an interdisciplinary research topic.…”
Section: Development Status Of Soasmentioning
confidence: 99%
“…[1][2][3][4][5][6] While the performance of these devices are now competitive with electronic-only interconnects and almost reach their theoretical limits, there still remain significant challenges to the realization of a complete integration of III-V lasers with silicon photonics components Several different approaches have been taken to integrate III-V lasers into the silicon photonic platform. [7][8][9][10][11][12][13] Among them, butt-joint coupling between the active III-V lasers and gain chip devices with passive silicon photonics components has drawn large attention recently due to the simplicity and high coupling efficiency, and it has been demonstrated that the silicon photonics integration can be effectively achieved by the butt-joint coupling of III-V quantum well (QW) and quantum dot (QD) gain chips and lasers with silicon photonics distributed Bragg reflectors (DBRs), modulators and waveguides, which have shown promising results for the optical interconnections. [11,12,[14][15][16][17][18] However, in the butt-joint coupling schematics, due to the presence of small air gap between the laser output facet and waveguide input, there is optical reflection at the laser facet/air and waveguide/air interface to provide optical feedbacks to the laser cavities, which can significantly affect the laser stability and performances.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Among them, butt-joint coupling between the active III-V lasers and gain chip devices with passive silicon photonics components has drawn large attention recently due to the simplicity and high coupling efficiency, and it has been demonstrated that the silicon photonics integration can be effectively achieved by the butt-joint coupling of III-V quantum well (QW) and quantum dot (QD) gain chips and lasers with silicon photonics distributed Bragg reflectors (DBRs), modulators and waveguides, which have shown promising results for the optical interconnections. [11,12,[14][15][16][17][18] However, in the butt-joint coupling schematics, due to the presence of small air gap between the laser output facet and waveguide input, there is optical reflection at the laser facet/air and waveguide/air interface to provide optical feedbacks to the laser cavities, which can significantly affect the laser stability and performances. [19][20][21][22] These issues have been investigated in the integrated photonics and telecommunication industries when coupling laser devices with other optoelectronics components, however, little attentions in this regards have yet been made in the silicon photonics integrations.…”
Section: Introductionmentioning
confidence: 99%